İNTRAKRANYAL TÜBERKÜLOMLARI OLAN BİR OLGUNUN KLİNİK VE MR ÖZELLİKLERİ - APAYDIN, Hülya; PELİN, Zerrin and ÖZEKMEKÇİ, Sibel and KOÇER, Naci (Cerrahpaşa Medical Journal, 2014)
Background. Intracranial tuberculomas are rare in industrialized countries, but still prevail their significance in developing nations. This paper presents a case of intracerebral tuberculoma with special emphasis on clinical characteristics and MRI findings. Observation. An 18 yearold woman was referred for evaluation of subacutely developed paraplegia, weight loss, nocturnal fever and raised intracranial pressure symptoms. Her paraplegia was attributed to an intracranial parasagittal lesion in the absence of sensory level and sphincter dysfunction. MRI of the brain showed numerous lesions located in the cerebral hemispheres, thalamus, cerebellum and brain stem as well as in parasagittal region which were compatible with tuberculomas. The tuberculomas were isointense on T1weighted images and hyperintense with central hypointensity on T2weighted images. Although the patient had no pulmonary symptoms, her chest Xray and chest CAT showed miliary pattern. Following treatment with corticosteroids and antituberculous medication with four firstline agents, the patient improved rapidly and was able to walk without help within one week. All of her symptoms resolved within one month despite the slow resolution of tuberculomas on MRI. Unexpectedly we remarked a paradoxical enlargement of one of these lesions under therapy. intracranial tuberculomas should be considered in patients with progressively developing focal neurological deficits or raised intracranial pressure symptoms and space occupying lesions on MRI.